Intention to use Islamic banking products and its determinants / Nur A'dila Mohd Faizal - Mohd Faizal, Nur A'dila (Faculty of Business Management, 2018)
Islamic financing has experienced worldwide acceptance and by early 2003 there were at least 176 Islamic banks around the world. Islamic banking are welcoming to both Muslim and non-Muslim customers. This study was conducted to determine the factors that influence intention to use Islamic banking products. This research will use quantitative approach and using primary data with distributes the questionnaire to residents of Taman Sri Andalas. The data will be collected within one month. This questionnaire will be focus on independent variables (attitude, religious, knowledge and social influence). The survey was conducted on 150 respondents to make sure at least 90 questionnaires are collected. Method of data analysis is using SPSS version 22.0 to analyse the data of descriptive analysis, reliability test (Cronbach's Alpha), Pearson correlation analysis and regession analysis. The results, there have positive influence between attitude and intention while it contra for religious, knowledge and social influence factors towards intention to use Islamic banking products.